Antimicrobial Resistance in Bacteria From Livestock and Companion Animals 2018
DOI: 10.1128/9781555819804.ch13
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance inEscherichia coli

Abstract: Multidrug resistance in Escherichia coli has become a worrying issue that is increasingly observed in human but also in veterinary medicine worldwide. E. coli is intrinsically susceptible to almost all clinically relevant antimicrobial agents, but this bacterial species has a great capacity to accumulate resistance genes, mostly through horizontal gene transfer. The most problematic mechanisms in E. coli correspond to the acquisition of genes coding for extended-spectrum β-lactamases (conferring resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(121 citation statements)
references
References 279 publications
(69 reference statements)
3
114
0
4
Order By: Relevance
“…Antimicrobial resistance is one of the major global threats to public and animal health (Poirel et al, ). The emergence and rapid spread of MDR and XDR bacteria is causing public concerns around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial resistance is one of the major global threats to public and animal health (Poirel et al, ). The emergence and rapid spread of MDR and XDR bacteria is causing public concerns around the world.…”
Section: Introductionmentioning
confidence: 99%
“…The results were shown in Table 3 Interestingly, there is evidence that ESBL E. coli has a higher level of mcr-1 than non-ESBL E. coli, and the rapid rise in ESBL also significantly increases the selective pressure for colistin resistance [17]. In this study, 63.6% (21/33) of MCRPEC strains were detected to contain different ESBL genes E. coli is by nature sensitive to almost all clinically relevant antimicrobial agents, but this bacterium has a great capacity to accumulate resistance genes, mainly through horizontal gene transfer [36]. In this study, 11 plasmids carrying non-lactam genes were found in MCRPEC, including fluoroquinolone (qnrA, qnrB, qnrS, aac(6')-Ib-cr), tetracycline (tetA, tetB), sulfonamide (sul1, sul2), aminoglycoside (aadA), and chloramphenicol (floR), suggesting that the effect of MCRPEC on spreading non-β-lactam genes should not be underestimated.…”
Section: Coexistence Of Mcr-1 Gene In Plasmids With β-Lactamase Antimmentioning
confidence: 62%
“…Therefore, finding the CTZ resistance without ESBL production in this study suggested selection of oxyiminocephalosporin (3GC) by other mechanisms of β-lactam resistance such as production of other β-lactamases, change in cell wall permeability, expression of active efflux pumps, gene mutations and/or alteration of penicillin binding protein receptors. 2,7,33 However, production of AmpC could be the mechanism by which the 6 FOXresistant isolates in this study preferred to CTZ since resistance to ESCs is mediated majorly by ESBL and/or AmpC which confers FOX resistance. 7,10,11,25 The finding of 30% FOX-resistant (putative AmpC-producers) E. coli in this study also calls for concern because AmpC-P enterobacteria are MDR as also observed in the current experiment.…”
Section: Discussionmentioning
confidence: 86%
“…Escherichia coli, a member of Enterobacterales is a natural inhabitant of the intestinal tract of humans and animals and thus found in various ecological niches such as soil, water, vegetables and so on. [1][2][3] Escherichia coli is a useful indicator organism for antimicrobial resistance surveillance (because it easily acquires and transfers resistance genes) and it is versatile, being facultatively pathogenic with the pathogenic variants associated with intestinal (enteritis) and extra-intestinal infections, including urinary tract infection, meningitis, peritonitis, and septicemia in humans. 1,2,4 Extendedspectrum cephalosporins (ESCs) which include the third (e.g., ceftazidime, cefpodoxime), fourth and fifth generation cephalosporins, and cephamycin (cefoxitin: FOX) are critically-important antibacterial agents of the highest priority in managing serious E. coli infections in humans and animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation